2018
DOI: 10.1177/2048872618798226
|View full text |Cite
|
Sign up to set email alerts
|

Octogenarian women with acute coronary syndrome present frailty and readmissions more frequently than men

Abstract: In octogenarians with acute coronary syndrome female sex was independently associated with death/hospitalisation at 6 months. Frailty was more common in women and was a predictor of poor prognosis. In men prefrailty also predicted a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
1
24
0
1
Order By: Relevance
“…Recently, we and other investigators have shown that frailty status is associated with inhospital and mid-term mortality in patients with acute coronary syndrome. 9,15,16 However, there have been few reports about changes in frailty status, which we addressed in this study. This study demonstrated that more than 40% of nonagenarians with AMI undergoing PCI were frail at admission and the proportion of patients with frailty clearly increased during hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we and other investigators have shown that frailty status is associated with inhospital and mid-term mortality in patients with acute coronary syndrome. 9,15,16 However, there have been few reports about changes in frailty status, which we addressed in this study. This study demonstrated that more than 40% of nonagenarians with AMI undergoing PCI were frail at admission and the proportion of patients with frailty clearly increased during hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, inhospital major bleeding and inhospital death occurred in 15.6% (BARC type 3 11.4%; BARC type 5 4.2%) and 17.7% (cardiac death 16.7%; non-cardiac death 1.0%) of patients, respectively ( Figure 2(a)). The median duration of hospitalisation was 15.5 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) days.…”
Section: Inhospital Outcomesmentioning
confidence: 99%
“…Finally, Vicent, et al (60) in an octogenarian Spanish population of 535 patients with STEMI found that female sex was independently associated with death and hospitalisation at 6-month follow-up.…”
Section: Myocardial Infarction With Non-obstructed Coronary Arteriesmentioning
confidence: 94%
“…Moreover, a third of patients with ACS are frail and a quarter of those ≥75 years are severely frail 16. Female sex independently predicts frailty among elderly patients with ACS, and frail women are at high risk of death despite ACS treatment 17…”
Section: Age At Disease Manifestation and Risk Profilementioning
confidence: 99%